The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/1750-3841.15747
|View full text |Cite
|
Sign up to set email alerts
|

Aichi virus inactivation by heat in 2‐ml glass vials

Abstract: Aichi virus (AiV) that results in gastroenteritis worldwide, is spread through contaminated shellfish and water. The resistance/tolerance of AiV to common inactivation processes along with the absence of commercially available vaccines makes it necessary to study its thermal inactivation kinetics. This research evaluated the heat inactivation of AiV in cell-culture media using 2-ml sterile glass vials by the linear and Weibull models. Heat treatments of AiV titers of 7 log plaque forming units (PFU)/ml were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…In order to determine inactivation parameters, models such as the linear regression model provide standards to estimate D ‐values, that is, time (min) required to cause 1 log PFU/mL reduction of infectious viruses that can predict the treatment conditions (time) required for higher log reductions (Ailavadi et al., 2021; Bozkurt et al., 2013). The calculated D ‐values for FCV‐F9 with D = 0.82 ± 0.01 min and TV of D = 0.96 ± 0.08 min with ~1 ppm ozone treatment within clear sterile water samples (Table 4) demonstrated that the linear D ‐values were close for FCV‐F9 and TV inactivation at RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine inactivation parameters, models such as the linear regression model provide standards to estimate D ‐values, that is, time (min) required to cause 1 log PFU/mL reduction of infectious viruses that can predict the treatment conditions (time) required for higher log reductions (Ailavadi et al., 2021; Bozkurt et al., 2013). The calculated D ‐values for FCV‐F9 with D = 0.82 ± 0.01 min and TV of D = 0.96 ± 0.08 min with ~1 ppm ozone treatment within clear sterile water samples (Table 4) demonstrated that the linear D ‐values were close for FCV‐F9 and TV inactivation at RT.…”
Section: Discussionmentioning
confidence: 99%
“…This linear line equation has a "slope of −1/D, where the number of viral survivors in PFU/mL after an exposure time t (min) is described as N(t) that has an initial viral population of N 0 " (Bozkurt et al, 2013;Patwardhan et al, 2020;Ailavadi et al, 2019Ailavadi et al, , 2021. The D (min)-value is then derived from this equation as the time of treatment that is needed to reduce the initial target viral population by 10-fold (Ailavadi et al, 2021).…”
Section: Parameters For Modeling Inactivation Of Fcv-f9 and Tv By ~1 ...mentioning
confidence: 99%